Quantum Superposition of Media Messages: Assessing Sustenance and Collapse Trigger of Contradictory Beliefs Across Climate Change, Political Narratives, and AI Discourses in Nigeria - Samuel Sunday Ameh; Nathan Oguche Emmanuel; Precious Ojocheneyo Ugbaje; Nworie Chukwuebuka Stephen; Raphael Chijioke EZE (Universitas Negeri Yogyakarta, 2026)
This study applies quantum cognition frameworks to investigate how Nigerian media audiences sustain contradictory beliefs (